Perioperative FOLFOX4 plus bevacizumab for initially unresectable advanced colorectal cancer (NAVIGATE-CRC-01) - Suenaga, Mitsukuni (Onco Targets Ther, 2015)
BACKGROUND: Perioperative chemotherapy combined with surgery for liver metastases is considered an active strategy in metastatic colorectal cancer (CRC). However, its impact on initially unresectable, previously untreated advanced CRC, regardless of concurrent metastases, remains to be clarified. METHODS: A Phase II study was conducted to evaluate the safety and efficacy of perioperative FOLFOX4 plus bevacizumab for initially unresectable advanced CRC. Patients with previously untreated advanced colon or rectal cancer initially diagnosed as unresectable advanced CRC (TNM stage IIIb, IIIc, or IV) but potentially resectable after neoadjuvant chemotherapy (NAC) were studied. Preoperatively, patients received six cycles of NAC (five cycles of neoadjuvant FOLFOX4 plus bevacizumab followed by one cycle of FOLFOX4 alone). The interval between the last dose of bevacizumab and surgery was at least 5 weeks. Six cycles of adjuvant FOLFOX4 plus bevacizumab were given after surgery. The completion rate of NAC and feasibility of curative surgery were the primary endpoints. RESULTS: An interim analysis was performed at the end of NAC in the 12th patient to assess the completion rate of NAC. The median follow-up time was 56 months. The characteristics of the patients were as follows: sex, eight males and four females; tumor location, sigmoid colon in three, ascending colon in one, and rectum (above the peritoneal reflection) in eight; stage, III in eight and IV in four (liver or lymph nodes). All patients completed six cycles of NAC. There were no treatment-related severe adverse events or deaths. An objective response to NAC was achieved in nine patients (75%), and no disease progression was observed. Eleven patients underwent curative tumor resection, including metastatic lesions. In December 2012, this Phase II study was terminated because of slow registration. CONCLUSION: Perioperative FOLFOX4 plus bevacizumab is well tolerated and has a promising response rate leading to curative surgery, which offers a survival benefit in initially unresectable advanced CRC with concurrent metastatic lesions.